Estimating degradation of strength of neat PEEK and PEEK-CF laminates under cyclic loading by mechanical hysteresis loops (Fracture and Structural Integrity, 2023)
A method for assessing the degradation of mechanical properties of neat polyetheretherketone and its laminated composite reinforced with unidirectional carbon fibers is proposed. It is based on the calculation of the maximum and minimum strains in a cycle, as well as both dynamic and secant moduli estimated from mechanical hysteresis loops. These parameters reflect the material damage degree, enabling to predict its current mechanical state.
Keywords: Polyetheretherketone (PEEK); polymer composite material; fatigue; elastic modulus; strain; hysteresis loop; digital image correlation